(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The preparation of special educators requires more than knowledge of diagnostic categories and corrective techniques. Graduates must be able to interpret incomplete evidence, recognise learner strengths and environmental barriers, design an inclusive response, communicate with learners, families and interdisciplinary professionals, use assistive and digital tools, and revise decisions after feedback. This article develops a methodology for forming practical competence through corrective-developmental cases and professional simulations. The study is theoretical and design-oriented; it combines analysis of inclusive education frameworks, competence mapping, synthesis of case-based and simulation-based learning research, and pedagogical modelling. Six competence components are operationalised: diagnostic-analytical, corrective-design, procedural-practical, communicative-collaborative, digital-assistive, and reflective-ethical. The proposed methodology follows eight connected stages: competence mapping, case briefing, diagnostic reasoning, decision design, simulated performance, structured debriefing, redesign and reperformance, and transfer assessment. A taxonomy of cases and simulation formats is presented, together with pedagogical conditions, evidence sources and four developmental levels. The central design principle is that a realistic scenario alone does not guarantee learning. Effective practice requires graduated scaffolding, explicit learner voice, individual accountability, structured debriefing, repeated performance, accessibility and human oversight of consequential decisions. Assessment triangulates case rationale, performance observation, communication evidence, accessible products, reflection, revision history and a new transfer case rather than equating clicks or completion with competence. The methodology provides a traceable foundation for future expert validation, pilot implementation and quasi-experimental testing without claiming completed empirical effects.